CRITERIA FOR ASSESSMENT OF COMPETITIVENESS OF HIGHER EDUCATIONAL INSTITUTIONS IN THE WORLD ECONOMY - A. Tisyachin; O. Mihaylov (Вестник университета)
In the article criteria of an estimation of competitiveness of the higher educational institutions applied at drawing up of the international ratings are considered, and the comparative estimation of weight of used indicators is carried out. On the basis of the study, conclusions and suggestions on improving the content of the criteria for international ratings are formulated.